THE IMPACT OF PRICE ON THE COMPETITIVE ADVANTAGES OF AN ENTERPRISE IN A MARKET ECONOMY - TRUNINA, Iryna; LATYSHEV, Kostiantyn; KUSHCH, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article explores the role of pricing as a crucial determinant of enterprise competitiveness within a market economy. The study highlights the place of pricing policy in the broader framework of competitive strategies and examines how pricing decisions influence both product attractiveness and long-term market positioning. Various pricing strategies are analyzed, including cost leadership, premium pricing, market penetration, skimming, and dynamic approaches, with attention to their advantages, limitations, and implications for competitive performance. The article also presents the sequence of stages in pricing policy formation, emphasizing the importance of systematic analysis of market conditions, consumer behavior, costs, and competitor actions. A special focus is given to future prospects for effective pricing policy. The study discusses the shift toward value-based pricing, and the trend toward personalization of offers. The article also addresses the impact of sustainability on pricing decisions, underlining the increasing willingness of consumers to pay more for environmentally responsible and socially conscious products. Overall, the findings indicate that pricing policy should not be treated merely as a financial calculation but as a multidimensional strategic tool. By leveraging customer-centric approaches, enterprises can strengthen their competitive advantages and ensure long-term success in a dynamic and uncertain global marketplace.